Multirate DelPHI to secure multirate ad hoc networks against wormhole attacks. (April 2018) - Qazi, Shams; Raad, Raad; Mu, Yi; Susilo, Willy
Abstract: DelPHI [1] is a highly cited protocol that secures Ad hoc On Demand Distance Vector (AODV) routing protocol against wormhole attacks. DelPHI assumes that the underlying wireless transmission rate is constant. Under such an assumption it has a wormhole detection rate above 80%. In this work we show that DelPHI is unable to secure AODV in a multirate transmission environment because it does not take into account the variable bit rate nature of the wireless channel and assumes a constant bit rate leading to either false detection or no detection of wormhole attacks. We go on to propose an extension to DelPHI (M-DelPHI) that adapts it to the multirate 802.11 wireless channel. We propose three fundamental extensions: 1. Multirate channel, 2. Processing delay and 3. Neighbour monitoring. We provide 2 test cases that demonstrate our extension and simulate the new protocol in different environments. We show that M-DelPHI performs exceptionally well resulting in above 90% wormhole detection rate against inbound and out-of-band wormholes under the specified test conditions.